The influence of Ali (may Allah be pleased with him) on interpretation: The influence of Ali (may Allah be pleased with him) on interpretation (Journal of the College of Education for Women, 2019)
Abstract:Through the research, I have briefly discussed the life of Imam Ali andindicated the interpretation of the Qur'an by language and terminology, theimportance and characteristics of Sahabas', may Allah be pleased with them,interpretation of the Qur'an. Also, the sayings of Imam Ali, wich included theexplanatory interpretation of the Qur'an by the Qura'n, Sunnah, language, andcorrect opinion. I have also indicated the reasons of the Quran's revelationand the readings of the Qura'n that had been received from him including theinterpretive meaning these readings revealed. Finally, I concluded myresearch with the most important results and recommends.